2011
DOI: 10.4049/jimmunol.1004088
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase IKKε Is a Potential Target for the Treatment of Inflammatory Hyperalgesia

Abstract: Inhibitor-κB kinase ε (IKKε) was only recently identified as an enzyme with high homology to the classical I-κB kinase subunits, IKKα and IKKβ. Despite this similarity, it is mainly discussed as a repressor of viral infections by modulating type I IFNs. However, in vitro studies also showed that IKKε plays a role in the regulation of NF-κB activity, but the distinct mechanisms of IKKε-mediated NF-κB activation are not clear. Given the paramount role of NF-κB in inflammation, we investigated the regulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Thus, a limitation of our study was not being able to avoid the influence of the prevention of weight gain on the reduced NF-kB signaling and atherosclerosis in the DK mice. In spite of that, we could still reach an agreement that IKKε is a bridge between obesity and inflammation [33] and in many inflammatory diseases IKKε takes effect through the activation of NF-kB pathway signaling [22][23]. Further investigation is warranted to clarify the direct regulatory mechanism between IKKε and atherosclerosis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, a limitation of our study was not being able to avoid the influence of the prevention of weight gain on the reduced NF-kB signaling and atherosclerosis in the DK mice. In spite of that, we could still reach an agreement that IKKε is a bridge between obesity and inflammation [33] and in many inflammatory diseases IKKε takes effect through the activation of NF-kB pathway signaling [22][23]. Further investigation is warranted to clarify the direct regulatory mechanism between IKKε and atherosclerosis.…”
Section: Discussionmentioning
confidence: 89%
“…This observation provided us with a new link between IKKε and HFD-induced atherosclerosis [21]. Furthermore, several studies have also suggested the potential role of IKKε in inflammatory pain, rheumatoid arthritis and osteoarthritis through the NF-κB activation cascade [22][23]. In this study, we therefore investigated whether IKKε plays a critical role in the initiation and progression of atherosclerosis through activation of the NF-κB pathway.…”
Section: Introductionmentioning
confidence: 93%
“…27, 28 TNF signaling and NF- κ B are associated with both acute and chronic pain. 29, 30, 31, 32, 33, 34, 35 The transcriptional consequences of TNFR signaling and NF- κ B activation in damage-sensitized nociceptive sensory neurons, however, remain unclear.…”
mentioning
confidence: 99%
“…unchanged amount of IKKb protein, total and phosphorylated, in the spinal cord after nerve injury and the only weak and transient increase of phosphorylated IkBa at this site. We showed recently that NF-kB activation in the spinal cord after nociceptive stimulation strongly depended on the IKK-related kinase IKKε, 33 which was abundantly expressed in neurons and glia 33 and might adopt some of the stimulus-dependent NF-kB activation at this site and may also be involved in the glia activation in the spinal cord after nerve injury.…”
Section: Discussionmentioning
confidence: 99%